The Effect of Online Customer Review, Service Quality, Promotion and Electronic Word of Mouth on Purchase Decisions on the Shopee Marketplace - Harnovinsah, Harnovinsah; Permana, Erwin (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the effect of Online Customer Review, EService Quality, Trust and Word of Mouth on Purchasing Decisions. The object of this study was students of the Faculty of Economics and Business, Pancasila University as consumers who had made purchases on the Shopee marketplace. The sampling technique used was Purposive Sampling with a sample size of 100 respondents from students of the Faculty of Economics and Business, Pancasila University as consumers who use Shopee. The data collection technique used a questionnaire distributed via Google Form to consumers of the Shopee marketplace at the Faculty of Economics and Business, Pancasila University. Data processing using IBM SPSS 25.0. Based on the results of the study, it shows that Online Customer Review has a positive and significant effect on Purchasing Decisions, E-Service Quality has a positive and significant effect on Purchasing Decisions, Trust has a positive and significant effect on Purchasing Decisions, Word of Mouth has a positive and significant effect on Purchasing Decisions and simultaneously the variables Online Customer Review, E-Service Quality, Trust and Word of Mouth have a positive and significant effect on Purchasing Decisions.